PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS VI SD MELALUI MODEL PEMBELAJARAN TGT BERBANTUAN MEDIA SNAKES AND LADDERS - Aditya, Danang Dwi; Nurwulandari, Ika; Rofiq, Muhammad Aunur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning outcomes on column multiplication among fourth-grade students at SDN 1 Todanan were initially low. Students struggled to memorize basic multiplication facts, lacked confidence in solving problems, and showed low participation during learning activities. This study aimed to improve students’ mathematics achievement through the implementation of the Teams Games Tournament (TGT) learning model supported by Snakes and Ladders media. The research applied a Classroom Action Research design based on the Kemmis and McTaggart model, carried out in two cycles. The participants were 23 fourth-grade students at SDN 1 Todanan. Data were collected through tests, observations, interviews, and documentation. Quantitative data were analyzed using mean scores, and mastery learning percentages, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The findings indicated a consistent improvement in learning outcomes across cycles. The mean score increased from 58.12 in the pre-cycle to 69 in Cycle I and 78.5 in Cycle II. The mastery learning percentage rose from 47.83% to 82.61%. It was concluded that the TGT model supported by Snakes and Ladders media effectively improved students’ mathematics learning outcomes.